Consumer intentions and willingness to pay for seaweed-fed cow's milk: The impact of attitude, knowledge, taste, and price - Sujita Pandey; Mausam Budhathoki; Marianne Thomsen (Future Foods)
Seaweed in dairy cow feed reduces methane emissions and enhances milk quality, providing a sustainable solution with the potential to boost sales in the climate-friendly market. This study aims to explore the market potential for this differentiated product, focusing on consumers' willingness to pay and examining how knowledge, attitudes, price, and taste toward climate-friendly products influence their purchasing intentions. The study was conducted using online surveys, with data collected from 428 participants in Denmark. The survey data were analysed using Covariance-based Structural Equation Modelling to identify predictors of purchase intentions. Results indicate that consumer attitudes and perceived taste were the strongest predictors of intentions to buy seaweed-fed cow's milk, while knowledge and price did not significantly influence purchase intentions. Additionally, knowledge significantly and negatively moderated the relationship between attitude and intention. Although taste did not significantly affect attitude, the price had a significant negative impact on attitude. On average, consumers were willing to pay 7.4 Danish Kroner (€0.99) more for seaweed-fed cow milk than for regular milk. The study concludes that introducing seaweed-fed milk is both feasible and commercially promising. By focusing on positive consumer attitudes, superior taste, and environmental benefits, dairy producers can effectively market this differentiated food product.